Appeals against detention in conditions of excessive security: an analysis of cases from medium secure units in Scotland - Bennett, Daniel M (The journal of forensic psychiatry & psychology, 2025)
In Scotland, patients have the right to appeal against not only the order which detains them in hospital but also, if treated in medium or high security, against the level of security in which they are treated. This is the first study to examine the characteristics of those appealing against treatment in conditions of medium security. We examined 94 cases of appeals against treatment in medium security of which 79 led to a decision by the Mental Health Tribunal for Scotland. Seventy-seven percent of appeals were successful. The support of the responsible medical officer, being placed on the transfer list from medium security and having a history of substance misuse were all significantly associated with successful appeals. There was variation between the three Scottish medium secure units in the likelihood of an appeal to succeed, which may relate to their specific circumstances. This work is important in understanding the factors which are likely to lead to successful appeals and may be of interest if the provision is extended within Scotland, as recently proposed by a review of mental health legislation, or beyond into other jurisdictions.